A conservation science agenda for a changing Upper Midwest and Great Plains, United States. Issue 8 (13th June 2020) - Ahlering, Marissa A.; Cornett, Meredith; Blann, Kristen; White, Mark; Lenhart, Christian; Dixon, Cami; Dudash, Michele R.; Johnson, Lucinda; Keeler, Bonnie; Palik, Brian; Pastor, John; Sterner, Robert W.; et al.
Abstract: The long‐term well‐being of both people and nature is achievable, assuming major changes in resource distribution and consumption at a global level. This optimistic outlook for the world requires rapid identification of major knowledge gaps that would undermine our ability to achieve a sustainable future if left unaddressed locally and regionally. Our goal was to identify the science needs that would make the biggest contribution to sustaining human society and natural systems in the Upper Midwest and Great Plains, United States. We engaged an interdisciplinary group of scientists and practitioners in an iterative exploration and prioritization process. The resulting list of 50 research questions identified science gaps for strategy implementation to achieve conservation success. Of the original list, 17 questions ranked as highly important in the region. These 17 questions constitute a conservation science agenda for the region. We call for alignment around this common agenda and a concerted, multidisciplinary approach to addressing these priority scientific needs.